Assessing the Customer Satisfaction of Cafe Kusina Using Dineserv Model: Towards a Guide: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the customer satisfaction of Café Kusina restaurantusing the DINESERV model in terms of reliability, assurance, tangibility, empathy, andresponsiveness.The results of the study reveal that the assessment of Customer Satisfaction of Café Kusinawas “very satisfied” in terms of product and place; the utilization of the DINESERV model inassessing the customer satisfaction of Café Kusina “strongly agrees” with terms of tangibility,empathy, and responsiveness; the most common problem encountered by the customers ofCafé Kusina was there are no enough parking lots; and there is a guideline proposed by theresearchers to improve the customer satisfaction of Café Kusina based on the result ofDINESERV model.Based on the result presented, the following are the recommendations: maintain theiratmosphere where customers will still feel comfortable; adding and offering coupons anddiscounts could make the customers more satisfied; consider planning on providing parkingspace for customers; and implement new guidelines that could help and improve the customersatisfaction of Cafe Kusina.
Keywords: Business